Ondansetron: a potential intervention for improving clinical outcomes in stroke patients - Xu, Jian; Zhang, Mengfei; Tao, Leyu; Zhang, Shuying; Tang, Zhihua (Frontiers in Pharmacology, 2025)
BackgroundStroke is a major global public - health problem. It is a cerebrovascular disease with sudden onset, high prevalence, and high rates of death and disability. Ondansetron (a 5 - HT3 receptor antagonist) an antiemetic, has recently been indicated in studies to have the ability to influence neurotransmitter imbalance, towardly have more effective against vomiting in stroke patients. However, its impact on stroke patients’ clinical outcomes remains unclear. This study uses real - world data to evaluate ondansetron’s effect on stroke patients’ clinical outcomes. Findings could lead to new treatments and better outcomes.MethodsThis study was a retrospective cohort analysis involving adult patients who experienced a stroke, categorized into two groups: the ondansetron group and the non-ondansetron group. To ensure the baseline characteristics were balanced, propensity score matching (PSM) was utilized. The mortality rate was assessed using multivariable Cox regression models along with Kaplan-Meier survival curves. Additionally, subgroup analyses were performed to examine the consistency of the findings.ResultsA total of 5,297 stroke patients were included in this study, among which 3,926 stroke patients received ondansetron treatment on the first day of admission to the intensive care unit (ICU), and 1,371 did not receive this drug treatment. After PSM, 2,628 patients were paired. The analysis results showed that the use of ondansetron on the first day of admission to the ICU significantly reduced the 30-day mortality rate (hazard ratio [HR] 0.73, 95% confidence interval [CI]: 0.59–0.92, P < 0.05). Meanwhile, the 60-day mortality rate also decreased significantly (HR 0.73, 95% CI: 0.60–0.90, P < 0.05).ConclusionTreatment using ondansetron is linked to an enhancement in the overall prognosis for stroke patients. Those who are administered ondansetron on the initial day of their ICU admission experience a notably lower mortality rate. The results of this research provide a compelling and valuable addition to the conventional stroke treatment protocol, holding considerable clinical importance and scientific research relevance.